Perbandingan Proses Ekstraksi Virgin Coconut Oil (VCO) - Eri Marwati; Fahmi Sadik (LPPM Universitas Abdurrab, 2023)
Coconut planted (Cocos nucifera L.) was one of the commodities that had high economic valued if managed properly. The numbered of coconut planted that grew could have used as superior products and high economic valued, one of which was by being used as virgin coconut oil or Virgin Coconut Oil. Better recognition of the beneficial health effects of coconut oil, especially virgin coconut oil is praised for its beneficial properties. The purpose of this studied was to determine the comparison of made VCO (virgin coconut oil) with or without the addition of pineapple filtrate. This researched is an experimental researched with the method of made VCO with variations in the addition of pineapple filtrate and without pineapple filtrate. The results showed the highest yield in VCO with the addition of pineapple filtrate 28%, the highest moisture content in VCO without the addition of pineapple filtrate 0.29%, the average free fatty acid content had the same value of 0.512%, the highest total plate numbered in VCO without the addition of pineapple filtrate 626 CFU/ml as well as positively contained alkaloids and saponins. The addition of pineapple filtrate could affect the yield of VCO produced but it needed to considered for its quality to met SNI and APCC quality requirements.